Experiences of foreign residents during COVID-19 pandemic in Taiwan - Purnima Pandey; Mei-Kuei Yu (Elsevier, 2022)
This study presents a survey analysis of the experiences of foreigners residing in Taiwan during the outbreak of the COVID-19 pandemic. Therein, we conducted interviews with 20 foreign residents of different nationalities in Taiwan. We shed light on participants' expectations and experiences of living in Taiwan during a pandemic. As for analysis, we inductively analyzed various essential parameters, such as identifying categories, themes, and outlines, mainly from the surveyed data associated with the interviews. In this course, five relevant themes have appeared, namely (I) Access to proper care (II) Living environment (III) Psychosocial effects, (IV) Workplace Environment, (V) Impact of borders closure. The study concludes that foreign residents' experiences during COVID-19 in Taiwan are admirable. The foreign residents feel comfortable, safe, and happy to stay and work in Taiwan because of the Taiwan government's policy towards successfully preventing community outbreaks.